Pengaruh Upah Minimum dan Inflasi terhadap Penyerapan Tenaga Kerja di Indonesia - Vicy Andriany; Sonya Aprimayana; Annisa Desfikasari (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2025)
This study aims to analyze the significance level of the influence of minimum wages and inflation on labor absorption in Indonesia. The research applies a quantitative approach with field research design using secondary data in the form of time series published by the Central Bureau of Statistics (BPS) for the period 1993–2023. Data collection was carried out through documentation methods, while data analysis employed multiple linear regression processed using EViews 12 software.The results indicate that, partially, the minimum wage variable has a positive and significant effect on labor absorption in Indonesia. This finding suggests that an increase in the minimum wage contributes to higher employment absorption during the study period. In contrast, the inflation variable shows a positive relationship but does not significantly affect labor absorption. This implies that rising inflation does not directly reduce or increase employment opportunities in a statistically significant manner. Simultaneously, minimum wages and inflation jointly have a significant impact on labor absorption.These findings highlight the crucial role of wage policy in maintaining labor market stability, while the effect of inflation tends to be indirect. Therefore, the government is expected to formulate adaptive minimum wage policies that take inflation into account to create a balance between workers’ welfare and the sustainability of employment opportunities.